2011
DOI: 10.4103/0022-3859.90091
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine-induced petechial rash

Abstract: A patient of essential hypertension stabilized on 10 mg amlodipine once daily developed brownish black petechial non-blanching macular rash bilaterally covering the limbs below the knee and dorsum of the feet. History, general and clinical examinations and lab investigations revealed no abnormalities. Temporal association of the onset of rash with amlodipine use, inability to explain rash by natural history of hypertension, possibility of rash with amlodipine and rash resolution on dechallenge placed this reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…ADRs are known to commonly manifest on the skin as this study reflects this which is similar to other studies [ 8,10].These are mainly due to hypersensitivity reactions such as skin rash and pruritus which is a reflection of the immunologic functions of the skin [10, 16, 18. Cutaneous adverse drug reaction are commonly due to unknown medication just as this study showed two patients with hyperpigmentation due to an unknown medication, however the suspected drug is likely to be amlodipine since it was the drug both patients had in common [16]. Hyperpigmentation due to amlodipine has been reported in case reports as seen in this study [19,20]. The exact mechanism of pigment formation is unknown but generally mechanisms of drug induced skin pigmentation has been proposed to occur by stimulation of melanin synthesis and its accumulation worsened by sun exposure or degradation of the drug and its uptake by dermal macrophages.…”
Section: Discussionsupporting
confidence: 53%
“…ADRs are known to commonly manifest on the skin as this study reflects this which is similar to other studies [ 8,10].These are mainly due to hypersensitivity reactions such as skin rash and pruritus which is a reflection of the immunologic functions of the skin [10, 16, 18. Cutaneous adverse drug reaction are commonly due to unknown medication just as this study showed two patients with hyperpigmentation due to an unknown medication, however the suspected drug is likely to be amlodipine since it was the drug both patients had in common [16]. Hyperpigmentation due to amlodipine has been reported in case reports as seen in this study [19,20]. The exact mechanism of pigment formation is unknown but generally mechanisms of drug induced skin pigmentation has been proposed to occur by stimulation of melanin synthesis and its accumulation worsened by sun exposure or degradation of the drug and its uptake by dermal macrophages.…”
Section: Discussionsupporting
confidence: 53%
“…Six percent of those who developed angioedema were assigned to amlodipine [9]. Amlodipine has also been reported causing petechial rash on lower limbs bilaterally in a woman [10]. The authors concluded that the rash was not due to vasculitis, because the patient had no other symptoms or abnormalities in lab results.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic reactions are rare, but recognized, side effects of many drugs [1][2][3][4][5][6][7]. These reactions can be toxic, metabolic, or allergic in nature.…”
Section: Discussionmentioning
confidence: 99%